Pearson’s peacekeepers : Canada and the United Nations Emergency Force, 1956-1967 - Carroll, Michael (My University, 2009)
In 1957 Lester Pearson won the Nobel Peace Prize for creating the United Nations Emergency Force during the Suez Crisis. A crowning achievement in a distinguished career, the award also established Canada’s reputation as a peacekeeping nation. Was this reputation earned, or do accounts of Canadian peacekeeping reside in the realm of national myths that obscure complex historical realities? Pearson’s Peacekeepers explores the reality behind the rhetoric by offering a comprehensive account of the UN’s first major peacekeeping operation. The UNEF eased tensions and kept peace along the Egyptian-Israeli border for more than a decade. Yet peacekeeping has never been easy, and this mission was no exception: it faced tremendous challenges in its creation, its funding, and during daily operations. And the UN’s inability to imagine, let along manage, the withdrawal of peacekeeping paved the way for further hostilities between Israel and Egypt during the Six Day War. By providing a nuanced account of Canada’s participation in the UNEF, this book not only challenges perceived notions of Canada’s past, it helps to more accurately evaluate international peacekeeping efforts in the present. It will appeal to students of history and political science and to veterans and general readers interested in peacekeeping, the Middle East, international diplomacy, and Canadian military and diplomatic history.
Keywords: United Nations Emergency Force; peacekeeping; Canada